What gets suppliers to play and who gets the pay? On the antecedents and outcomes of collaboration in retailer-supplier dyads. Issue 2 (5th August 2014) - Rossiter Hofer, Adriana; Hofer, Christian; A. Waller, Matthew
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to adopt and contribute to the further development of the relational view by examining the drivers of retailer-supplier collaboration and its effect on the performance of both the retailer and the supplier. Design/methodology/approach – The paper draws its conclusions from a structural analysis of dyadic survey data collected from consumer packaged goods suppliers and retailers in Brazil. In addition, objective retailer performance measures (retailer in-stock performance) are included in the data set. Findings – The results indicate that a supplier's customer orientation is an important determinant of supplier relationship-specific investments and, ultimately, supply chain collaboration. The empirical results also indicate that retailers stand to benefit the most from a supplier's collaborative efforts. In addition, there is evidence that a supplier's customer orientation is positively related to its own performance. Research limitations/implications – The limited sample size – a result of the dyadic nature of the data – constitutes a limitation and, at the same time, presents opportunities for future, larger-scale studies. Nonetheless, this study highlights the value of customer orientation and collaboration in terms of driving performance outcomes for both suppliers and buyers, while invoking the notion that the benefits of supply chain collaboration accrue differentially over time from the retailers' and suppliers' perspectives. Originality/value – While many of the relationships set forth in this research have been implicitly assumed by proponents of the relational view, this study furthers the development of the relational view by explicitly modeling supplier relationship-specific investments and customer orientation as antecedents of collaboration. Moreover, the study contributes to the literature on buyer-supplier collaboration by simultaneously exploring to what extent both suppliers and retailers derive benefits from such collaboration.